Geoenvironmental mapping of the city of Casa Branca (SP), Brazil, as a subsidy to territorial planning - Reis, Fábio Augusto Gomes Vieira [UNESP]; Do Amaral, Ana Maria Carrascosa [UNESP]; Do Carmo Giordano, Lucilia [UNESP]; Dos Santos Corrêa, Claudia Vanessa [UNESP]; Chaves, Camila Jardinetti [UNESP] (My University, 2018)
Even though geoenvironmental studies are recent, they are increasingly gaining importance as an environmental planning tool. At the beginning of the planning process, the planner compartmentalizes the given space, in order to better understand the parts that compose the environment. Then, he or she integrates each part to understand how they interact with each other in order to optimize them. The present project aims to develop geo-environmental zoning in the city of Casa Branca, São Paulo, Brazil at a scale of 1:50.000, considering physiographic, geological/geotechnical, and land use and occupancy criteria, including the location of Permanent Preservation Areas (PPAs). A cross-thematic analysis was the technique used for zoning. A series of thematic maps were drawn up and then subsequently crossed, either directly or in specific associations, until a final summary map was reached. The methodological steps of the zoning processes included: a physiographic subdivision of the area, the mapping of land cover and use, the location of the PPAs, fieldwork, and lastly, the integration of the information obtained. After executing all of the project stages, the map showing the geo-environmental units of the study area was obtained, from which interpretations were made about the potential and the limitations of the area, as well as recommendations. Overall, the aim of the study was to assist in planning and decisions regarding environmental issues in addition to providing a database for future environmental research in the area.
Mapeamento geoambiental do município de Casa Branca (SP) como subsídio ao planejamento territorial
Keywords: Cross-thematic analysis; Environmental planning; Geoenvironmental units; Physiographic subdivision